Теория и практика технологий терморазведки на базе данных многоспектральных космических съемок - Винниченко, Н.К.; Винниченко, О.Н.; Глущенко, И.В.; Степченко, В.Н.; Багрянцев, В.А. (Геоінформатика, 2015)
На базе современных знаний о физике тепловых процессов, происходящих в геосреде, системно изложены термодинамические основы методов терморазведки на материалах дистанционных наблюдений в оптическом, инфракрасном диапазонах и радиодиапазоне электромагнитных волн. С использованием немногочисленых разрозненных публикаций сделана попытка популяризации основных принципов, послуживших отправной точкой для создания методов и технологий интроскопии (геотомографии), применение которых позволяет осуществлять зондирование Земли практически на произвольно заданную глубину, что дает возможность определять структуру и термодинамику среды. В частности, дано представление о методе видеотепловизионной генерализации Р.Д. Мухамедьярова, составляющем основу упомянутых технологий, что в некоторой степени восполнит пробел в научной периодике по заданной теме. Рассмотрены конкретные примеры применения технологии тепловой геотомографии, разработанной Специальным центром аэрокосмических технологий (г. Днепропетровск), для решения разноплановых геоструктурных и поисковых задач нефтегазового направления в различных условиях и разных регионах земного шара. Отмечено, что термодинамические особенности геосреды могут служить прямым индикатором наличия залежей углеводородов. Это отличает дистанционную терморазведку от других геофизических методов. На засадах сучасних знань про фізику теплових процесів, які відбуваються у геосередовищі, системно викладено термодинамічні основи методів терморозвідки на матеріалах дистанційних спостережень в оптичному, інфрачервоному діапазонах і радіодіапазоні елетромагнітних хвиль. На підставі нечисленних розрізнених публікацій зроблено спробу популяризації основних принципів, які слугували відправною точкою для створення методів і технологій інтроскопії (геотомографіі), застосування яких дає змогу здійснювати зондування Землі практично на довільно задану глибину, що дає можливість визначати структуру і термодинаміку геосередовища. Зокрема, подано уявлення про метод відеотепловізійної генералізації Р.Д. Мухамедьярова, який складає основу згаданих технологій, що деякою мірою заповнить прогалину у науковій періодиці за зазначеною темою. Розглянуто конкретні приклади застосування технології теплової геотомографіі, розробленої “Спеціальним центром аерокосмічних технологій” (м. Дніпропетровськ), для вирішення різноманітних геоструктурних та пошукових завдань нафтогазового напряму в різних умовах і різних регіонах земної кулі. Встановлено, що термодинамічні особливості геосередовища можуть слугувати прямим індикатором наявності покладів вуглеводнів. Це відрізняє дистанційну терморозвідку від інших геофізичних методів. Purpose. The purpose of the paper is to present a systemic exposition, based on modern concepts of the physics of thermal processes in geologic environment, of the thermodynamic foundation of geothermal exploration methods based on remote monitoring in the optical, infrared and radio wavelengths of electromagnetic waves. To popularize basic principles that have served as the starting point for the creation of methods and introscopy technologies (geotomography), which significantly increase the amount of information on the structure and thermodynamics of geologic environment that complements data from other geophysical methods.
Design/methodology/approach. The technology of thermal introscopy (geotomography) the results of which are presented, rests on the R.D. Muhamedjarov’s “Method of video thermovision generalization”. Technology allows us to conduct sensing of the Earth at a near arbitrary depth, which in terms of Petroleum Geology permits to determine not only the localization of hydrocarbon deposits but also their nature.
Findings. The publication significantly contributes to the scientific literature on the subject because the primary sources used in it are scattered and few. Examples of application of the thermal geotomography technology by developed “Special Center of Aerospace Technologies” (Dnepropetrovsk, Ukraine), which are widely presented in the article, show high efficiency of its solutions for diverse geostructural and search problems of oil and gas areas. Of special attention is the possibility to indicate HC directly.
Practical value/implications. The practical advantages primarily related to the tact that it is possible to apply the technology independent from terrain conditions; the technology is also environmentally clean, efficient, of relatively low cost, and of high success rate.